Acute effects of plyometric intervention—Performance improvement and related changes in sprinting gait variability - Mackala, K.; Fostiak, M. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to examine the effect of a short high-intensity plyometric program on the improvement of explosive power of lower extremities and sprint performance as well as changes in sprinting stride variability in male sprinters. Fourteen healthy male sprinters (mean ± SD: age: 18.07 ± 0.73 years, body mass: 73 ± 9.14 kg, height: 180.57 ± 8.16 cm, and best 100 m: 10.89 ± 0.23) participated in the experiment. The experimental protocol included vertical jumping such as squat jump, countermovement jump, and horizontal jumps; standing long jump and standing triple jumps to assess lower-body power, maximal running velocity; a 20-m flying start sprint that evaluated variability of 10 running steps and 60-m starting block sprint. All analyzed parameters were obtained using the new technology of OptoJump-Microgate (OptoJump, Italy). The short-term plyometric training program significantly increased the explosive power of lower extremities, both vertical and horizontal jumping improvement. However, the vertical jumps increased much more than the horizontal. The 20-m improvements were derived from an increase of stride frequency from 4.31 to 4.39 Hz because of a decrease of ground contact time from 138 to 133 milliseconds. This did not translate into step length changes. Therefore, the significantly increased frequency of stride (1.8%), which is a specific expression of ground contact time reduction during support phase, resulted in an increase of speed. The training volume of 2 weeks (with 6 sessions) using high-intensity (between 180 and 250 jumps per session) plyometric exercises can be recommended as the short-term strategy that will optimize one's probability of reaching strong improvements in explosive power and sprint velocity performance.